The Penyuluhan Pola Makan DASH bagi Lansia sebagai Strategi Pengendalian Hipertensi di Banda Aceh: Penyuluhan Pola Makan DASH bagi Lansia sebagai Strategi Pengendalian Hipertensi di Banda Aceh - Rosa Galica Gita Gressia; Nurul Hadi; Juanita Juanita2 (Jurnal Pengabdian Kesehatan Komunitas, 2025)
Hypertension is common among older adults and can lead to serious complications such as stroke and heart failure. One non-pharmacological effort to control it is the application of the Dietary Approaches to Stop Hypertension (DASH) diet. This activity aimed to improve older adults’ knowledge and skills in implementing the DASH eating pattern. The method used was educational demonstration with a participatory approach, conducted in Banda Raya Subdistrict, Banda Aceh City. The activities included lectures, demonstrations, and redemonstrations using videos, posters, leaflets, and examples of DASH menus. The results showed increased understanding and interest among participants in adopting healthy eating patterns. The demonstration method proved effective in raising older adults’ awareness of blood pressure control. Evaluation results showed that 75% of participants were able to recall the main principles of the DASH diet, 80% could mention three recommended foods and three foods that should be reduced, and 85% were interested in applying it at home. Participants also demonstrated changes in attitude, with a stronger commitment to reducing the consumption of fatty foods. This activity ran smoothly, was interactive, and succeeded in improving older adults’ knowledge, attitudes, and interest in implementing healthy eating patterns as a non-pharmacological effort to control blood pressure. Thus, the demonstration method proved effective in increasing older adults’ awareness of the importance of hypertension control through the DASH diet. Abstrak Hipertensi sering dialami lansia dan dapat menimbulkan komplikasi serius seperti stroke dan gagal jantung. Salah satu upaya nonfarmakologis untuk mengendalikannya dengan penerapan Dietary Approaches to Stop Hypertension (DASH). Kegiatan ini bertujuan meningkatkan pengetahuan dan keterampilan lansia dalam menerapkan pola makan DASH. Metode yang digunakan adalah demonstrasi edukatif dengan pendekatan partisipatif, dilaksanakan Kecamatan Banda Raya, Kota Banda Aceh. Kegiatan meliputi ceramah, demonstrasi, dan redemonstrasi dengan media video, poster, leaflet, serta contoh menu DASH. Hasil menunjukkan peningkatan pemahaman dan minat peserta dalam menerapkan pola makan sehat. Metode demonstrasi terbukti efektif meningkatkan kesadaran lansia terhadap pengendalian tekanan darah. Hasil evaluasi  menunjukkan  bahwa  75%  peserta  mampu mengingat prinsip utama diet DASH, 80% dapat menyebutkan tiga makanan yang dianjurkan dan tiga yang perlu dikurangi, serta 85% berminat menerapkannya di rumah. Peserta juga menunjukkan perubahan sikap dengan lebih berkomitmen dalam mengurangi konsumsi makanan berlemak. Kegiatan ini berjalan lancar, interaktif, dan berhasil meningkatkan pengetahuan, sikap, serta minat lansia dalam menerapkan pola makan sehat sebagai upaya nonfarmakologis pengendalian tekanan darah. Dengan demikian, metode demonstrasi terbukti efektif dalam meningkatkan kesadaran lansia terhadap pentingnya pengendalian hipertensi melalui pola makan DASH.